Economies of scale and density in urban rail transport: effects on productivity - Daniel J. Graham (2003)
This paper examines economies of scale and density in urban rail transport. It isolates the effects of constant and non-constant returns on output and productivity growth using data relating to 17 rail systems in cities around the world. Estimates reveal constant returns to scale but increasing returns to density. The productivity model shows that total factor productivity change has been of great importance in differentiating the output performance of urban rail systems. Our analysis of average labour productivity confirms the importance of shifts to other factors of production and technological change in explaining changing levels of output per worker.